Ypsolopha admirandella sp. n. (Lepidoptera: Ypsolophidae), a new European species from the steppes of Russia - Sachkov, Sergey A.; Zolotuhin, Vadim V. (Zootaxa, 2020)
A new species, Ypsolopha admirandella sp. nov., is described from clay-steppes of the Ulyanovsk Region (European Russia). The holotype of the new species is deposited in the collection of the Samara State University. The new species is associated with Ephedra distachya. The holotype and its genitalia, in addition those of the closely related Y. colleaguella Baraniak, 2007 are illustrated.